2017
DOI: 10.2147/opth.s119926
|View full text |Cite
|
Sign up to set email alerts
|

Meibomian gland dysfunction patients with novel Sjögren’s syndrome biomarkers benefit significantly from a single vectored thermal pulsation procedure: a retrospective analysis

Abstract: PurposeTo measure the effects from a single vectored thermal pulsation treatment of the meibomian glands on dry eye signs and symptoms in patients who tested positively versus negatively for novel Sjögren’s syndrome (SS) biomarkers.MethodsThe retrospective study included the deidentified data of 102 eyes of 59 patients with dry eye and meibomian gland dysfunction (MGD), who were also tested for novel biomarkers for SS and underwent a single 12-minute LipiFlow thermal pulsation procedure. All patients were alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
8
0
4
Order By: Relevance
“…It was also reported that the LipiFlow ® system produced successful results in patients with other conditions such as Sjögren syndrome (III) [ 45 ], dry eye after laser correction surgery (III) [ 41 ], and symptomatic contact lens wearers (I) [ 46 ].…”
Section: Warming Eyelid Devicesmentioning
confidence: 99%
“…It was also reported that the LipiFlow ® system produced successful results in patients with other conditions such as Sjögren syndrome (III) [ 45 ], dry eye after laser correction surgery (III) [ 41 ], and symptomatic contact lens wearers (I) [ 46 ].…”
Section: Warming Eyelid Devicesmentioning
confidence: 99%
“…The efficacy of a single VTP treatment in patients with MGD and dry eye is well established, 27 33 , 49 and VTP treatment has been shown to deliver a sustained treatment effect in multiple studies. 28 , 30 , 32 , 49 The majority of prior VTP studies have focused on treating MGD in dry eye populations, including Sjögren’s patients 32 and patients with refractory dry eye postrefractive surgery. 49 , 50 However, contact lens wearers with MGD are a natural study population for the VTP treatment of MGD due to 1) the demands that a contact lens places on the tear film, 1 13 2) the significant correlation of both severity and prevalence of MGD in contact lens wearers, 11 , 16 20 and 3) the consistently high contact lens dropout rate due to dry eye symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The device applies direct heat (42.5 C) to the palpebral conjunctiva of the upper and lower eyelids directly over the meibomian glands in order to soften meibum, while simultaneously applying pulsatile pressure to the outer eyelids with an inflatable air bladder that compresses the glands. 63,64 Case studies 63,65,66 as well as controlled 18,64,[67][68][69][70][71][72] and non-controlled [73][74][75][76][77] trials have shown that a single 12-minute VTP therapy can improve meibomian gland function, ocular surface staining, and tear film break-up time as well as relieve ocular symptoms (Table 3). Such improvement in meibomian gland function and dry eye symptoms achieved with a single VTP therapy session can be sustained for one to three years.…”
Section: Thermal Pulsation Systemmentioning
confidence: 99%
“…Such improvement in meibomian gland function and dry eye symptoms achieved with a single VTP therapy session can be sustained for one to three years. 68,74,77 The improvement in meibomian gland function induced by VTP therapy has been evaluated on the basis of the number of meibomian glands yielding liquid secretion (MGYLS) in the lower eyelid 63,[66][67][68][69][70]72,[75][76][77] or the meibomian gland secretion (MGS) score, 64,65,68,71,[73][74][75]77 which represents both the number of secreting meibomian glands and the quality of the secreted material as determined with a meibomian gland evaluator (MGE, Johnson & Johnson Vision). Some prospective trials have found that the lipid layer thickness of the tear film as determined with a LipiView interferometer (Johnson & Johnson Vision) did not change significantly at an average of 52 days or greater than three months after a single VTP therapy.…”
Section: Thermal Pulsation Systemmentioning
confidence: 99%